Design for healthy and active aging (Project Mee Reboot ) - Yu, Anqi (2016)
Mild cognitive impairment (MCI) in the aged may deteriorate into Alzheimer’s but this process could be slowed down or prevented by regular mental and physical exercise paired with a healthy diet. With Singapore’s elderly population tripling by 2030, Mee Reboot is designed to tackle this increasingly prevailing problem. Inspired by her volunteering days at St. Luke’s Eldercare and playing games with the elderly, the designer has designed an electric exercising totem along with a set of supporting infrastructures and phone application to motivate the elderly to engage in a healthy and active lifestyle that will slow the onset of MCI.